Data Visualization as a Means of Optimizing Control Systems Model in Project Management. (Global Journal of Computer Science and Technology, 2023)
Annotation- The article addresses current issues concerning the utilization of data visualization in project management within the project context It delves into the characteristics and principles of implementing projects within the project management framework of business entities The classification of processes within the project management system is outlined The study examines the significance of data visualization as a prerequisite for decision-making highlighting the traits of visual project management The tools employed for crafting visual representations of project data derived from project implementation outcomes are investigated Various types of infographics intended for monitoring the execution of project-related business tasks encompassing factors such as sequence resources and commencement and culmination dates are identified The article concludes by presenting the outcomes of generating visualizations using MS Project and MS Power BI within the realm of project management business processes in the project area
Keywords: software engineering; project management; project data; visualization